Enhancing Curriculum Monitoring Systems: Case Study of Arabic Language Education at STAIN Mandailing Natal - Erlina; Wahidmurni; Nurhadi; Rita Zahara Kamsir (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to evaluate the monitoring, supervision, and curriculum improvement system in the Arabic Language Education Study Program at Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN Madina), assessing its effectiveness in enhancing Arabic language competence and supporting Islamic learning. Utilizing a qualitative research design, the study employs a case study methodology, combining interviews, observations, and documentation analysis. The findings reveal that the monev system, involving comprehensive planning, implementation, and reporting, effectively covers graduate competency standards, content standards, process standards, and learning assessment standards. The structured approach, involving multiple stakeholders, ensures thorough evaluation and continuous improvement. However, limitations such as the need for more in-depth internal supervision of content standards and challenges related to human resources and stakeholder engagement were noted. These findings are significant for higher education institutions aiming to enhance their curriculum systems, offering a model for structured monitoring and supervision. Further research is recommended to explore integrated internal supervision mechanisms and long-term effects on student outcomes.